Zonificación de la capacidad portante del suelo del distrito de Morales - Rocha Sandoval, César Augusto (2010)
Peru is on the western edge of the South American continental plate beneath which the Nazca oceanic plate, consisting of a denser crust dives than the previous, almost frontally with a dip between 20 ° and 30 ° and with a velocity on about 10 cm. by year. The external manifestations of this process are the pit Marine Pacific, the Andes and the presence of some volcanoes in the southern Peru and northern Chile. The space-time of the epicentres of the earthquakes occurred in this territory distribution It shows that the same may be associated with: Interaction plates. eruptions of volcanoes. Geological faults. Most carvings are a result of geological surface orogenic movement, product to turn the process of lifting and fonnación of the Cordillera de los Andes, over geologic time. The Peruvian territory is therefore located in a seismically active area world, within the Circum-Pacific Belt. Since the formation of the continents has state under the action and effects of large earthquakes, of whose references only available from the espall.ola presence, based on stories and narratives, and from this century, with instrumental data. Based on this information have been prepared several studies, one of whose synthesis is Seismic Zoning Map of Peru, this map considers the Peruvian tenitory divided into three zones, according to the observed seismic and seismic potentiality each zone: Zone III: Seismicity Zona Alta Il: Seismicity Media Zone 1: Low Seismicity According to this zoning, the San Martin region is in the area Il (of average) seismicity. This study aims to conduct soil studies District Morales, finding the type of soil and its bearing capacity.